2020
DOI: 10.3390/ijms21228782
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Therapeutic Implications of microRNAs in Non-Small Cell Lung Cancer

Abstract: microRNAs (miRNAs), endogenous suppressors of target mRNAs, are deeply involved in every step of non-small cell lung cancer (NSCLC) development, from tumor initiation to progression and metastasis. They play roles in cell proliferation, apoptosis, angiogenesis, epithelial-to-mesenchymal transition, migration, invasion, and metastatic colonization, as well as immunosuppression. Due to their versatility, numerous attempts have been made to use miRNAs for clinical applications. miRNAs can be used as cancer subtyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 131 publications
(164 reference statements)
0
17
0
Order By: Relevance
“…By directly binding to the 3'-untranslated regions of their target genes, miRNAs can promote translation suppression or degrade mRNAs, thereby regulating gene expression (17). Additionally, miRNAs have an effect on the oncogenesis and progression of NSCLC by controlling a wide range of biological behaviours (18)(19)(20). lncRNAs can operate as competitive endogenous RNAs (ceRNAs) by competitively binding to miRNAs and weakening the miRNA-mediated inhibitory effects on mRNA expression, thereby controlling gene expression at the posttranslational level (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…By directly binding to the 3'-untranslated regions of their target genes, miRNAs can promote translation suppression or degrade mRNAs, thereby regulating gene expression (17). Additionally, miRNAs have an effect on the oncogenesis and progression of NSCLC by controlling a wide range of biological behaviours (18)(19)(20). lncRNAs can operate as competitive endogenous RNAs (ceRNAs) by competitively binding to miRNAs and weakening the miRNA-mediated inhibitory effects on mRNA expression, thereby controlling gene expression at the posttranslational level (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical outcome of NSCLC remains unsatisfactory due to the high metastasis and recurrence rates ( 4 ). It is well-known that miRNAs play important roles in the progression and development of several diseases, including cancers ( 21 23 ). For example, miR4766-5p, miR-1915-3p and miR-615-3p are associated with tumor development in gastric cancer ( 24 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the connections between inflammation, lung cancer and COVID-19, we surveyed the literature to evaluate possible epigenetic links. The roles of miRNAs in inflammation [ [202] , [203] , [204] , [205] , [206] , [207] , [208] ] and lung cancer [ [251] , [252] , [253] , [254] ] are well established, and recent literature suggests role of miRNAs in COVID-19 infections as well. For example, it has been suggested that immune responses to various viral respiratory infections, including COVID-19, are characterized by ectopic expression of miRNAs [ 255 ].…”
Section: Micrornas As Epigenetic Regulators Connecting Inflammation mentioning
confidence: 99%